A note coutioning against financial analysts' high reliance on profitability data: the case of the pharmaceutical and construction sectors in the UK - Abdullah, Shamsul Nahar (Universiti Utara Malaysia, 1999)
In this paper, the author puts forward several issues that need to be considered before a financial analyst can rely on profitability data when making inferences about a company's value. Two issues are addressed namely, the accrual accounting method and earnings management. In order to illustrate the issues, the author used the Ohlson's model (1991) which argued that the value of a firm is the sum of the book value of the equity and the present value of the expected future clean surplus residual income. To facilitate the illustration, the author selected two UK companies from the pharmaceutical sector and two UK companies from the construction sector. The two sectors were selected because they were affected differently by the application of the accrual accounting method. Generally, our evidence from the financial data supported intuitively Ohlson's model. In addition to using Ohlson's model, the author also discusses the issue of earnings management which potentially affects the usefulness of profitability data.